Perpetuating Evidence in Civil Law Proceedings - Morchadze, Zurab (European Scientific Journal, ESJ, 2022)
The civil law process is based on the principles of adversarial proceedings and disposition, and having complete information on these principles is crucial for the parties to the process. For example, even in an apparently "profitable" case, a party who did not take care of applying the perpetuating measures may not win anything, because at the time of enforcement of the ruling it may appear that the defendant has long since alienated her/his property, or if the party has not taken care of the request for evidence and the perpetuation of evidence in a timely manner, serious difficulties may arise in the consideration of the case and as a result, lose the case. Evidence is facts obtained from sources provided by law on the basis of which the parties defend their interests. The burden of proof at trial is shared equally between the parties. The parties try to prove their veracity in order to get the appropriate result. Therefore, the main purpose of the article is to focus on the importance of the perpetuation of evidence. The first chapter deals with the essence perpetuating evidence, the second chapter deals with the judge’s ruling according to which s/he can load the evidence with obligation even before the lawsuit is filed, the third chapter is devoted to the evaluation of evidence by the court and the judge’s inner conviction. The fourth chapter deals with the rule of appeal, which is one of the problematic issues of this paper.